Serological evidence of possible human infection with Tioman virus, a newly described paramyxovirus of bat origin - Yaiw, K.C.; Crameri, Gary; Wang, L.; Chong, Heng Thay; Chua, Kaw Bing; Tan, Chong Tin; Goh, Khean Jin; Shamala, Devi; Wong, K.T. (Oxford University Press, 2007)
Tioman virus, a relatively new paramyxovirus, was isolated from fruit bats (Pteropus species) on Tioman Island, Malaysia, in 2001. The objective of this study was to determine the prevalence of antibodies to T. virus in island inhabitants, by use of comparative ELISA and serum neutralization assays. Of the 169 human sera analyzed, 5 (approximately 3.0%) were positive for T. virus, by comparative ELISA. Of these 5 sera, 3 (1.8% of the total) had neutralizing antibodies against T. virus, suggesting previous infection of this study population by this virus or a similar virus.